Criatividade, autonomia e precariedade : o trabalho dos profissionais em tecnologia da informação - Martins, Amanda Coelho (2016)
Labor relations that comes from the transformations of recent decades after the productive restructuring process, with the crisis of the Fordist-Taylorist model, guide a new arrangement in work and production organization, marked by reflections about flaxibilization process. With a highlight on autonomy and work individualization, which expose the workers to risks, challenges, and encourage detachment through entrepreneurship capability. Different ways of remuneration, self-employment, "PJotismo" (workers who operate with legal person bond) and similars, may mask precariousness of attachment, as well as forms of indirect subordination - resulting from market pressures for continuous updating, customers who participate in the projects preparation, and from the companies in which they are inserted, with implications on working hours. The research objectives were to analyze the notions of creativity, autonomy and immateriality in the discourse about software workers, manifested in concrete labor relations; understand how supervision and control of these workers manifest and to understand in what point there is the internalization of the innovation and flexibility discourse by these workers. Semi-structured interviews were conducted with the workers. The research was conducted with employees of IT companies in the cities of Araraquara-SP, São Carlos-SP and Bauru-SP, as well as workers who operate as trainees, as PJs and with fellowships in the first two cities.